If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 14 = 7x + -12 Reorder the terms: 14 + -6x = 7x + -12 Reorder the terms: 14 + -6x = -12 + 7x Solving 14 + -6x = -12 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 14 + -6x + -7x = -12 + 7x + -7x Combine like terms: -6x + -7x = -13x 14 + -13x = -12 + 7x + -7x Combine like terms: 7x + -7x = 0 14 + -13x = -12 + 0 14 + -13x = -12 Add '-14' to each side of the equation. 14 + -14 + -13x = -12 + -14 Combine like terms: 14 + -14 = 0 0 + -13x = -12 + -14 -13x = -12 + -14 Combine like terms: -12 + -14 = -26 -13x = -26 Divide each side by '-13'. x = 2 Simplifying x = 2
| (3n-12)=6 | | y=(x+6)(x-7) | | x^4+-29x^2+100=0 | | (-3n)/5-6=0 | | 18x^2=12+15x | | 4x+17=3(x+1)+21 | | (3n-20)/2=11 | | 2-7(x+1)-5(x+2)= | | 6(1-2)=1 | | 6r^2-r-2=0 | | x^2-29x+100=0 | | 6(1-2)= | | x/2=2/5(4-x)-4 | | 10x=4x^2-1 | | 9n-5=6n+10 | | x+y+3a=-3 | | -5-(-7)= | | 8(z-3)=-24 | | 12x+7+11x=2x+5+21x | | p^2-2p=2 | | -5(-2)(7)(-1)= | | 6-3x=7(4-2x) | | x-y+a=-1 | | x^2=4+3x | | 56-x-x^2=0 | | 5280x=66*1.446 | | -4.9t^2+10t+2=8 | | t^2=2t+15 | | 4x+8(-6)=-24 | | 10x+40-3x=98-9x-26 | | 64-9x^2=0 | | r^2-4r+3=0 |